PENILAIAN PENGAJARAN GURU PELATIH MENGGUNAKAN âLESSON NOTEâ - Iksan, Zanaton H. (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Teaching and learning processes involving various events that happened so fast, involving interaction between students, teachers and teaching materials. In this process, the evaluation of teaching is needed, especially for teachers who are doing teaching practice in schools. However, the assessment made less meaningful, particularly when there is no evidence that can be used during discussion after teaching session. Teachers trainers will require a detailed and in-depth evaluation of each element in the teaching and learning process. Thus, this study aims to get teachersâ reflection on the use of Lesson Note in the process of teaching evaluation by the supervisor. Observations during the process of teaching and learning will be done to the teachers during practical teaching at the school. Written note by using Lesson Note application during the observation is to reflect on teaching process starting from the beginning until the end of the lesson. Picture and written notes was made in Lesson Note Application for important things that would to be discussed; for examples concept, teaching activities, and interaction between teacher-student. After teaching, discussion will be held with by using the evident (picture and written notes) that have been taken using the Lesson Note application. At the end of the semester, teacher trainers give some reflection on the assessment using Lesson Note. These studies have impact on the quality of teaching future teachers when they input a deep and detailed assessment. Hence, teacher trainers could improve their teaching techniques to make their teaching practices for future.